Dialogue in the Book of signs : a polyvalent analysis of John 1:19-12:50 - Thomaskutty, Johnson. (Biblical Interpretation Series, 2015)
Dialogue in the Book of Signs offers a polyvalent analysis of John 1:19-12:50 at the micro-, meso-, and macro-levels. With the help of several synchronic methods, including genre, narrative, rhetorical, and dramatic studies, the author analyzes the content, form, and function of John's dialogue. Thus, the divine-human dialogue, which is interwoven within the text, provides a key to the understanding of the dialogue between the narrator and the reader. In this volume, after setting a background and a theoretical framework, an extensive exploration of dialogue at the exchange, episode, and narrative levels is offered. The connection of dialogue with other literary aspects such as monologues, signs, I AM sayings, and metaphors is also established. Thus, this study provides a comprehensive understanding of dialogue in John 1-12.